Phage single-gene lysis: Finding the weak spot in the bacterial cell wall - Chamakura, Karthik (J Biol Chem, 2019)
In general, the last step in the vegetative cycle of bacterial viruses, or bacteriophages, is lysis of the host. dsDNA phages require multiple lysis proteins, including at least one enzyme that degrades the cell wall (peptidoglycan (PG)). In contrast, the lytic ssDNA and ssRNA phages have a single lysis protein that achieves cell lysis without enzymatically degrading the PG. Here, we review four “single-gene lysis” or Sgl proteins. Three of the Sgls block bacterial cell wall synthesis by binding to and inhibiting several enzymes in the PG precursor pathway. The target of the fourth Sgl, L from bacteriophage MS2, is still unknown, but we review evidence indicating that it is likely a protein involved in maintaining cell wall integrity. Although only a few phage genomes are available to date, the ssRNA Leviviridae are a rich source of novel Sgls, which may facilitate further unraveling of bacterial cell wall biosynthesis and discovery of new antibacterial agents.